THE HISTORY OF LOCAL GOVERNMENT RADIO IN KUANTAN TENGAH DISTRICT KUANTAN SINGINGI REGENCY 2000-2014 - Zeni Safitri Zeni Safitri; Ridwan Melay Ridwan Melay; Marwoto Saiman Marwoto Saiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: With the development of science and technology and is also encouraging progress in many ways. One in the field of information and communication, in which information and communication media have a very important role in public life, both as a means of education and entertainment information. Kuantan Singingi regency local government radio is a radio for the first time, radio presence was well received by the public and government, so raise the government sharply and make this radio as a local public radio that initially only the private radio station founded by young boys of the village Taluk Kuantan. Kuantan Singingi regency radio local governments play an important role in the lives of people Kuantan Singingi regency at this time, namely as a source of information, where the public information about the event that occurred in Kuantan Singingi regency can obtain. But it is also in the entertainment, especially with regard tu culture Kuantan Singingi regency as a pacu jalur, randai and so on.Keywords : Radio Local Government.